Flexible fiber aerogel thermal insulation material as well as preparation method and application thereof
By impregnating cellulose nanocrystals in electrospinning and silicon alcohol solution, flexible fiber aerogel insulation materials with excellent mechanical fatigue resistance and high-temperature thermal insulation performance were prepared, solving the problems of powder loss and insufficient performance of existing materials. , suitable for high temperature and high pressure environments.
Patent Information
- Application Number
- CN202411443034.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-14
AI Technical Summary
The existing silica aerogel composite thermal insulation materials are prone to powder loss during transportation and assembly, and are not resistant to mechanical fatigue and high-temperature thermal insulation performance, so they cannot be suitable for high-temperature and high-pressure environments.
SiO2 nanofiber materials are prepared by electrospinning technology, and cellulose nanocrystals are impregnated in silicon alcohol solution, hydrophobic modification and solvent replacement, forming flexible fiber aerogel with excellent mechanical fatigue resistance and high-temperature thermal insulation performance Material.
It improves the mechanical fatigue resistance and high-temperature heat insulation properties of the material, reduces the powder drop rate, enhances the mechanical and mechanical properties, and is suitable for heating components in complex structures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to a flexible fiber aerogel thermal insulation material and a preparation method and application thereof. Background Art
[0002] Silica aerogel is a porous mesh structure material with nanoscale and high porosity. Its structure can effectively inhibit the heat conduction of gas and solid, so its thermal conductivity is very low. It is the most ideal thermal insulation material in the world today. However, due to the weak interface interaction between nanoparticles, silica aerogels usually have fragile properties, low mechanical strength and poor flexibility, which limits their wide application. It is in this situation that silica aerogel composite insulation materials came into being, and its appearance has attracted widespread attention and great attention in the industry.
[0003] Silica aerogel composite thermal insulation material is a high-performance composite material prepared by chemically or physically compounding silica aerogel with other inorganic or organic fibers. However, due to the relatively poor adhesion between silica aerogel particles and fiber reinforcements, the prepared composite material is prone to serious powder loss problems during transportation and assembly, which not only reduces the material's thermal insulation performance, but also threatens the health of related personnel; on the other hand, the existing silica aerogel composite thermal insulation material has relatively poor ablation resistance and cannot be used for thermal protection problems with long-term near-zero ablation in high temperature, high pressure, medium and high heat flow environments. The silica aerogel composite thermal insulation materials on the market still have more or less technical defects such as mechanical fatigue resistance and high-temperature thermal insulation performance that need to be further improved.
[0004] For example, the Chinese invention patent with application number 201010515083.X discloses a glass fiber reinforced silica aerogel composite material, which is a reinforced aerogel obtained by pre-treating glass fiber and compounding it with silica wet gel, then aging and drying. This reinforced aerogel composite material is prepared by using fiber as a reinforcing phase, which improves the mechanical properties of the aerogel, but the aerogel exists in powder form, and the connection between the aerogel and the fiber is not firm, and it is easy to pulverize and fall off during secondary processing.
[0005] It can be seen that the development of a flexible fiber aerogel insulation material with excellent mechanical fatigue resistance and high-temperature thermal insulation performance, low powder loss rate, and good mechanical properties, as well as its preparation method and application, meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of aerogel composite thermal insulation materials. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a flexible fiber aerogel insulation material with excellent mechanical fatigue resistance and high-temperature thermal insulation performance, low powder loss rate, and good mechanical properties, as well as a preparation method and application thereof.
[0007] The present invention provides a method for preparing a flexible fiber aerogel thermal insulation material, comprising the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 8 to 12 hours, and using a multi-energy field assisted treatment for 3 to 5 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 45-65°C for 4-6 hours, then heating to 800-1200°C at a heating rate of 4-6°C / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 2-4 hours to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water are mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution is adjusted to 2-3 with hydrochloric acid having a concentration of 0.8-1.2 mol / L, and then continuously magnetically stirred at room temperature for 20-25 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: impregnate the SiO2 nanofiber material and cellulose nanocrystal prepared in step S3 into the silanol solution prepared in step S4, then adjust the pH value to 6-8 with ammonia water with a concentration of 0.4-0.6 mol / L, and after uniform dispersion, seal and stand for aging at 35-45°C for 45-50 hours to obtain a silicon dioxide wet gel; then place the silicon dioxide wet gel in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then place it in ethanol for solvent replacement, and finally take out the wet gel after solvent replacement, and obtain a flexible fiber aerogel composite thermal insulation material after sufficient drying.
[0008] Preferably, the dispersant in step S1 is one of polyethylene oxide, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide.
[0009] Preferably, the polyethylene oxide is POLYOX WSR N-10 polyethylene oxide from Dow, USA.
[0010] Preferably, the mass ratio of the dispersant and the acidic aqueous solution in step S1 is (0.25-0.35):10.
[0011] Preferably, the acidic aqueous solution in step S1 is an aqueous nitric acid solution, and the mass percentage concentration of the acidic aqueous solution is 0.3-0.5%.
[0012] Preferably, in step S1, the mass ratio of methyltriethoxysilane, tetraethyl orthosilicate and organic solvent is 1:2.7:(8-12); the organic solvent is at least one of N,N-dimethylformamide and N,N-dimethylacetamide.
[0013] Preferably, in step S1, the mass ratio of the A dispersion to the B dispersion is 1:(1-2).
[0014] Preferably, the multi-energy field in step S1 is a superposition field of microwaves, steady magnetic fields and electromagnetic oscillation fields; the frequency of the microwaves is 2.0-2.5 GHz, and the power is 400-1000 W; the magnetic field strength of the steady magnetic field is 4000-6000 Gs; the frequency of the electromagnetic oscillation field is 10-20 Hz, and the medium and low duty cycles are 16-20%.
[0015] Preferably, the process parameters of the electrospinning in step S2 include: room temperature 20-26°C, relative humidity 27-33%, voltage 16-22kV, distance between needle tip and receiving device 18-22cm, needle tip swinging distance 90-110mm, injection needle inner diameter 0.51mm, constant feed speed 18-22ml / min, spinning 8-12h.
[0016] Preferably, the inert gas in step S3 is any one of nitrogen, helium, neon and argon.
[0017] Preferably, the molar ratio of tetraethyl orthosilicate, ethanol and water in step S4 is 1:(8-12):(4-7).
[0018] Preferably, the mass ratio of the SiO2 nanofiber material, cellulose nanocrystals and silanol solution in step S5 is (5-8):(1-2):100.
[0019] Preferably, the cellulose nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosyn Technology Co., Ltd.
[0020] Preferably, the mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 8-12%.
[0021] Preferably, the mass ratio of the silicon dioxide wet gel to the ethanol solution of trimethylchlorosilane in step S5 is 1:(4-6).
[0022] Preferably, the time for the hydrophobic modification in step S5 is 5-8 hours; and the time for the solvent replacement is 10-15 hours.
[0023] Preferably, the sufficient drying in step S5 is drying at 60-80° C. for 3-5 hours, washing with deionized water, and then drying at 120-230° C. for 4-6 hours.
[0024] Another object of the present invention is to provide a flexible fiber aerogel thermal insulation material made by the above-mentioned method for preparing a flexible fiber aerogel thermal insulation material.
[0025] Another object of the present invention is to provide an application of the flexible fiber aerogel thermal insulation material in heating components with complex structures.
[0026] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The method for preparing the flexible fiber aerogel thermal insulation material disclosed in the present invention has a simple process flow, convenient operation and control, high preparation efficiency and finished product qualification rate, low dependence on equipment, low energy consumption and capital investment, and is suitable for continuous large-scale production.
[0027] (2) The method for preparing the flexible fiber aerogel thermal insulation material disclosed in the present invention comprises the steps of preparing a spinning precursor mixture, electrospinning, calcination, preparing a silanol solution, preparing a flexible fiber aerogel composite thermal insulation material, etc. By rationally selecting the process parameters and sequence of each step, the prepared flexible fiber aerogel thermal insulation material has excellent mechanical fatigue resistance and high-temperature thermal insulation performance, low powder loss rate, and good mechanical properties.
[0028] (3) The flexible fiber aerogel thermal insulation material disclosed in the present invention uses silica nanofibers to reinforce silica aerogel. The homogeneous composite can enhance the adhesion and compatibility between the two, thereby improving the mechanical fatigue resistance and high-temperature thermal insulation performance of the product. Using nano-scale fibers instead of traditional micron-scale fibers as reinforcing materials can improve the flexibility of the product. The combined effect of the reinforcing material and the matrix material can significantly improve the brittleness of the aerogel, giving the product advantages such as low powder loss rate and good mechanical properties.
[0029] (4) The flexible fiber aerogel thermal insulation material disclosed in the present invention adopts a multi-energy field auxiliary treatment including microwaves with specific parameters, a steady magnetic field and an electromagnetic oscillation field in the preparation process of the spinning precursor mixture, which can improve the dispersion uniformity of the components in the mixture, improve the electrospinning effect, and further improve the mechanical properties and mechanical fatigue resistance of the final product; cellulose nanocrystals are also added in the preparation process of the flexible fiber aerogel composite thermal insulation material, which not only improves the compatibility between the components, but also enhances the mechanical properties, so that the manufactured product has better mechanical fatigue resistance and high-temperature thermal insulation performance, lower powder loss rate, and better mechanical properties. DETAILED DESCRIPTION
[0030] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0031] A method for preparing a flexible fiber aerogel thermal insulation material comprises the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 8 hours, and using a multi-energy field assisted treatment for 3 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 45°C for 4 hours, then heating to 800°C at a heating rate of 4°C / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 2 hours to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water are mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution is adjusted to 3 with hydrochloric acid having a concentration of 0.8 mol / L, and then continuously magnetically stirred at room temperature for 20 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: impregnate the SiO2 nanofiber material and cellulose nanocrystals prepared in step S3 into the silanol solution prepared in step S4, then adjust the pH value to 6 with 0.4 mol / L ammonia water, and after uniform dispersion, seal and stand for aging at 35°C for 45 hours to obtain a silicon dioxide wet gel; then place the silicon dioxide wet gel in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then place it in ethanol for solvent replacement, and finally take out the wet gel after solvent replacement, and obtain a flexible fiber aerogel composite thermal insulation material after sufficient drying.
[0032] The dispersant in step S1 is polyethylene oxide; the polyethylene oxide is POLYOX WSR N-10 polyethylene oxide from Dow, USA; the mass ratio of the dispersant to the acidic aqueous solution in step S1 is 0.25:10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.3%.
[0033] The mass ratio of methyltriethoxysilane, tetraethyl orthosilicate and organic solvent in step S1 is 1:2.7:8; the organic solvent is N,N-dimethylformamide; the mass ratio of dispersion A and dispersion B in step S1 is 1:1; the multi-energy field in step S1 is a superposition field of microwave, steady magnetic field and electromagnetic oscillation field; the frequency of the microwave is 2.0 GHz and the power is 400 W; the magnetic field strength of the steady magnetic field is 4000 Gs; the frequency of the electromagnetic oscillation field is 10 Hz, and the medium and low duty cycle is 16%.
[0034] The process parameters of the electrospinning in step S2 include: room temperature of 20°C, relative humidity of 27%, voltage of 16kV, distance between the needle tip and the receiving device of 18cm, needle tip swinging distance of 90mm, injection needle inner diameter of 0.51mm, constant feed speed of 18ml / min, and spinning for 8h.
[0035] The inert gas described in step S3 is nitrogen; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:8:4; the mass ratio of SiO2 nanofiber material, cellulose nanocrystals and silanol solution described in step S5 is 5:1:100; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0036] The mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 8%; the mass ratio of the silicon dioxide wet gel and the ethanol solution of trimethylchlorosilane in step S5 is 1:4; the time for hydrophobic modification in step S5 is 5 hours; the time for solvent replacement is 10 hours; the sufficient drying in step S5 is drying at 60°C for 5 hours, washing with deionized water, and then drying at 120°C for 6 hours.
[0037] A flexible fiber aerogel thermal insulation material made by adopting the preparation method of the flexible fiber aerogel thermal insulation material.
[0038] An application of the flexible fiber aerogel thermal insulation material on heating components with complex structures. Example 2
[0039] A method for preparing a flexible fiber aerogel thermal insulation material comprises the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 9 hours, and using a multi-energy field assisted treatment for 3.5 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 50° C. for 4.5 h, then heating to 900° C. at a heating rate of 4.5° C. / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 2.5 h to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water were mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution was adjusted to 2.7 with hydrochloric acid having a concentration of 0.9 mol / L, and then continuously magnetically stirred at room temperature for 22 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: the SiO2 nanofiber material and cellulose nanocrystals prepared in step S3 are impregnated into the silanol solution prepared in step S4, and then the pH value is adjusted to 6.5 with 0.45 mol / L ammonia water. After uniform dispersion, the mixture is sealed and aged at 38°C for 47 hours to obtain a wet silica gel; the wet silica gel is then placed in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then placed in ethanol for solvent replacement. Finally, the wet gel after solvent replacement is taken out, and after sufficient drying, a flexible fiber aerogel composite thermal insulation material is obtained.
[0040] The dispersant in step S1 is hexadecyltrimethylammonium chloride; the mass ratio of the dispersant to the acidic aqueous solution in step S1 is 0.28:10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.35%.
[0041] The mass ratio of methyltriethoxysilane, tetraethyl orthosilicate and organic solvent in step S1 is 1:2.7:9; the organic solvent is N,N-dimethylacetamide; the mass ratio of dispersion A and dispersion B in step S1 is 1:1.3; the multi-energy field in step S1 is a superposition field of microwave, steady magnetic field and electromagnetic oscillation field; the frequency of the microwave is 2.2 GHz and the power is 600 W; the magnetic field strength of the steady magnetic field is 4500 Gs; the frequency of the electromagnetic oscillation field is 13 Hz, and the medium and low duty cycle is 17%.
[0042] The process parameters of the electrospinning in step S2 include: room temperature 22°C, relative humidity 28%, voltage 18kV, distance between needle tip and receiving device 19cm, needle tip swing distance 95mm, injection needle inner diameter 0.51mm, constant feed speed 19ml / min, spinning 9h.
[0043] The inert gas described in step S3 is helium; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:9:5; the mass ratio of SiO2 nanofiber material, cellulose nanocrystals and silanol solution described in step S5 is 6:1.2:100; the length of the cellulose nanocrystals is 100-500nm and the diameter is 20-100nm, which is provided by Beijing Naxun Technology Co., Ltd.; the mass percentage concentration of the ethanol solution of trimethylchlorosilane described in step S5 is 9%.
[0044] The mass ratio of the silica wet gel and the ethanol solution of trimethylchlorosilane in step S5 is 1:4.5; the time for hydrophobic modification in step S5 is 6 hours; the time for solvent replacement is 12 hours; the sufficient drying in step S5 is drying at 65°C for 4.5 hours, washing with deionized water, and then drying at 160°C for 5.5 hours.
[0045] A flexible fiber aerogel thermal insulation material made by adopting the preparation method of the flexible fiber aerogel thermal insulation material.
[0046] An application of the flexible fiber aerogel thermal insulation material on heating components with complex structures. Example 3
[0047] A method for preparing a flexible fiber aerogel thermal insulation material comprises the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 10 hours, and using a multi-energy field assisted treatment for 4 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 55°C for 5 hours, then heating to 1000°C at a heating rate of 5°C / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 3 hours to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water were mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution was adjusted to 2.5 with hydrochloric acid having a concentration of 1 mol / L, and then continuously magnetically stirred at room temperature for 23 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: the SiO2 nanofiber material and cellulose nanocrystals prepared in step S3 are impregnated into the silanol solution prepared in step S4, and then the pH value is adjusted to 7 with 0.5 mol / L ammonia water. After uniform dispersion, the mixture is sealed and aged at 40°C for 48 hours to obtain a wet silica gel; the wet silica gel is then placed in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then placed in ethanol for solvent replacement. Finally, the wet gel after solvent replacement is taken out, and after sufficient drying, a flexible fiber aerogel composite thermal insulation material is obtained.
[0048] The dispersant described in step S1 is hexadecyltrimethylammonium bromide; the mass ratio of the dispersant and the acidic aqueous solution in step S1 is 0.3:10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.4%; the mass ratio of methyltriethoxysilane, tetraethyl orthosilicate, and organic solvent in step S1 is 1:2.7:10; the organic solvent is N,N-dimethylformamide; the mass ratio of the A dispersion and the B dispersion in step S1 is 1:1.5; the multi-energy field in step S1 is a superposition field of microwaves, steady magnetic fields, and electromagnetic oscillation fields; the frequency of the microwaves is 2.3 GHz, and the power is 700 W; the magnetic field strength of the steady magnetic field is 5000 Gs; the frequency of the electromagnetic oscillation field is 15 Hz, and the medium and low duty cycle is 18% at this time.
[0049] The process parameters of the electrospinning in step S2 include: room temperature 23°C, relative humidity 30%, voltage 19kV, distance between needle tip and receiving device 20cm, needle tip swing distance 100mm, injection needle inner diameter 0.51mm, constant feed speed 20ml / min, spinning 10h.
[0050] The inert gas described in step S3 is neon; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:10:5.5; the mass ratio of SiO2 nanofiber material, cellulose nanocrystals and silanol solution described in step S5 is 6.5:1.5:100; the cellulose nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0051] The mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 10%; the mass ratio of the silicon dioxide wet gel to the ethanol solution of trimethylchlorosilane in step S5 is 1:5; the time for hydrophobic modification in step S5 is 6.5 hours; the time for solvent replacement is 13 hours; the sufficient drying in step S5 is drying at 70°C for 4 hours, washing with deionized water, and then drying at 190°C for 5 hours.
[0052] A flexible fiber aerogel thermal insulation material made by adopting the preparation method of the flexible fiber aerogel thermal insulation material.
[0053] An application of the flexible fiber aerogel thermal insulation material on heating components with complex structures. Example 4
[0054] A method for preparing a flexible fiber aerogel thermal insulation material comprises the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 11 hours, and using a multi-energy field assisted treatment for 4.5 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 60° C. for 5.5 h, then heating to 1100° C. at a heating rate of 5.5° C. / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 3.5 h to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water were mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution was adjusted to 2.2 with hydrochloric acid having a concentration of 1.1 mol / L, and then continuously magnetically stirred at room temperature for 24 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: the SiO2 nanofiber material and cellulose nanocrystals prepared in step S3 are impregnated into the silanol solution prepared in step S4, and then the pH value is adjusted to 7.5 with 0.55 mol / L ammonia water. After uniform dispersion, the mixture is sealed and aged at 43°C for 49 hours to obtain a wet silica gel; the wet silica gel is then placed in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then placed in ethanol for solvent replacement. Finally, the wet gel after solvent replacement is taken out, and after sufficient drying, a flexible fiber aerogel composite thermal insulation material is obtained.
[0055] The dispersant in step S1 is polyethylene oxide; the polyethylene oxide is POLYOX WSR N-10 polyethylene oxide from Dow, USA; the mass ratio of the dispersant and the acidic aqueous solution in step S1 is 0.33:10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.45%; the mass ratio of methyltriethoxysilane, tetraethyl orthosilicate and organic solvent in step S1 is 1:2.7:11; the organic solvent is a mixture of N,N-dimethylformamide and N,N-dimethylacetamide in a mass ratio of 3:5; the mass ratio of the A dispersion and the B dispersion in step S1 is 1:1.8; the multi-energy field in step S1 is a superposition field of microwaves, steady magnetic fields and electromagnetic oscillation fields; the frequency of the microwaves is 2.4 GHz and the power is 900 W; the magnetic field strength of the steady magnetic field is 5800 Gs; the frequency of the electromagnetic oscillation field is 18 Hz, and the medium and low duty cycle is 19% at this time.
[0056] The process parameters of the electrospinning described in step S2 include: room temperature of 25°C, relative humidity of 32%, voltage of 21kV, distance between the needle tip and the receiving device of 21cm, needle tip swinging back and forth distance of 105mm, injection needle inner diameter of 0.51mm, constant feed speed of 21ml / min, spinning for 11h; the inert gas described in step S3 is argon; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:11:6.5; the mass ratio of SiO2 nanofiber material, cellulose nanocrystal and silanol solution described in step S5 is 7.5:1.8:100; the length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm, which is provided by Beijing Naxun Technology Co., Ltd.
[0057] The mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 11%; the mass ratio of the silicon dioxide wet gel to the ethanol solution of trimethylchlorosilane in step S5 is 1:5.5; the time for hydrophobic modification in step S5 is 7.5 hours; the time for solvent replacement is 14 hours; the sufficient drying in step S5 is drying at 75°C for 3.5 hours, washing with deionized water, and then drying at 220°C for 4.5 hours.
[0058] A flexible fiber aerogel thermal insulation material made by adopting the preparation method of the flexible fiber aerogel thermal insulation material.
[0059] An application of the flexible fiber aerogel thermal insulation material on heating components with complex structures. Example 5
[0060] A method for preparing a flexible fiber aerogel thermal insulation material comprises the following steps: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 12 hours, and using a multi-energy field assisted treatment for 5 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 65°C for 6 hours, then heating to 1200°C at a heating rate of 6°C / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 4 hours to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water are mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution is adjusted to 2 with hydrochloric acid having a concentration of 1.2 mol / L, and then continuously magnetically stirred at room temperature for 25 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: impregnate the SiO2 nanofiber material and cellulose nanocrystals prepared in step S3 into the silanol solution prepared in step S4, then adjust the pH value to 8 with 0.6 mol / L ammonia water, and after uniform dispersion, seal and stand for aging at 45°C for 50 hours to obtain a silicon dioxide wet gel; then place the silicon dioxide wet gel in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then place it in ethanol for solvent replacement, and finally take out the wet gel after solvent replacement, and obtain a flexible fiber aerogel composite thermal insulation material after sufficient drying.
[0061] The dispersant described in step S1 is polyethylene oxide; the polyethylene oxide is POLYOX WSR N-10 polyethylene oxide from Dow, USA; the mass ratio of the dispersant and the acidic aqueous solution in step S1 is 0.35:10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.5%; the mass ratio of methyltriethoxysilane, tetraethyl orthosilicate, and organic solvent in step S1 is 1:2.7:12; the organic solvent is N,N-dimethylformamide; the mass ratio of the A dispersion and the B dispersion in step S1 is 1:2; the multi-energy field in step S1 is a superposition field of microwaves, steady magnetic fields, and electromagnetic oscillation fields; the frequency of the microwaves is 2.5 GHz, and the power is 1000 W; the magnetic field strength of the steady magnetic field is 6000 Gs; the frequency of the electromagnetic oscillation field is 20 Hz, and the medium and low duty cycle is 20% at this time.
[0062] The process parameters of the electrospinning described in step S2 include: room temperature of 26°C, relative humidity of 33%, voltage of 22kV, distance between the needle tip and the receiving device of 22cm, needle tip swinging distance of 110mm, injection needle inner diameter of 0.51mm, constant feed speed of 22ml / min, spinning for 12h; the inert gas described in step S3 is nitrogen; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:12:7.
[0063] The mass ratio of the SiO2 nanofiber material, cellulose nanocrystals and silanol solution in step S5 is 8:2:100; the length of the cellulose nanocrystals is 100-500nm, the diameter is 20-100nm, and they are provided by Beijing Naxun Technology Co., Ltd.; the mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 12%; the mass ratio of the silica wet gel and the ethanol solution of trimethylchlorosilane in step S5 is 1:6; the time for hydrophobic modification in step S5 is 8h; the time for solvent replacement is 15h; the sufficient drying in step S5 is drying at 80°C for 3h, washing with deionized water, and then drying at 230°C for 4h.
[0064] A flexible fiber aerogel thermal insulation material made by adopting the preparation method of the flexible fiber aerogel thermal insulation material.
[0065] An application of the flexible fiber aerogel thermal insulation material on heating components with complex structures.
[0066] Comparative Example 1 A flexible fiber aerogel thermal insulation material and a preparation method thereof, which are basically the same as Example 1, except that there is no multi-energy field auxiliary treatment and the calcination temperature is 700°C.
[0067] Comparative Example 2 A flexible fiber aerogel thermal insulation material and a preparation method thereof, which are substantially the same as those of Example 1, except that cellulose nanocrystals are not added and there is no hydrophobic modification step.
[0068] In order to further illustrate the beneficial technical effects of the flexible fiber aerogel insulation materials involved in each embodiment of the present invention, relevant performance tests were carried out on the flexible fiber aerogel insulation materials involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: (1) High-temperature thermal insulation performance: Prepare a sample with a size of 200 mm × 200 mm × 25 mm, heat it at 350 °C for 10 min, and test the cold surface temperature. The lower the cold surface temperature, the better the high-temperature thermal insulation performance.
[0069] (2) Thermal stability: Heat each product at 350°C for 1 hour, cool to room temperature, weigh and compare the material mass before and after heating. If there is no mass loss, the thermal stability is qualified, otherwise it fails.
[0070] (3) Powder loss test: Each thermal insulation material was treated with a vibrating screen with a vibration frequency of 120 rad / s for 10 minutes, and the powder loss rate (the ratio of the weight of the fallen powder to the weight of the raw material) was tested. A powder loss rate lower than 0.1% was considered to be free of powder loss.
[0071] (4) Mechanical fatigue resistance: After each product is subjected to 1000 cycles of bending test, observe whether the sample has obvious cracks. If there are no obvious cracks, the mechanical fatigue resistance has passed, otherwise it has failed.
[0072] (5) Tensile strength: Tested in accordance with the provisions of Chapter 9 of GB / T 17911-2006.
[0073] It can be seen from Table 1 that the flexible fiber aerogel thermal insulation materials disclosed in the embodiments of the present invention have better high-temperature thermal insulation performance, thermal stability, mechanical fatigue resistance and tensile strength than the comparative example products, and have a lower powder loss rate; the combined use of multi-energy field assisted treatment, cellulose nanocrystals, and hydrophobic modification steps and the reasonable selection of calcination temperature are beneficial to improving the above properties.
[0074] Table 1
[0075] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a flexible fiber aerogel thermal insulation material, characterized in that: The steps include: Step S1, preparation of a spinning precursor mixture: uniformly dispersing a dispersant in an acidic aqueous solution to obtain a dispersion A; uniformly dispersing methyltriethoxysilane and tetraethyl orthosilicate in an organic solvent to obtain a dispersion B; mixing the dispersion A and the dispersion B, sealing and stirring at room temperature for 8 to 12 hours, and using a multi-energy field assisted treatment for 3 to 5 minutes to obtain a spinning precursor mixture; Step S2, electrostatic spinning: electrospinning the spinning precursor mixture prepared in step S1 to prepare a precursor nanofiber material; Step S3, calcination: drying the precursor nanofiber material prepared in step S2 in a vacuum drying oven at 45-65°C for 4-6 hours, then heating to 800-1200°C at a heating rate of 4-6°C / min under the protection of an inert gas atmosphere, and calcining at a constant temperature for 2-4 hours to form a SiO2 nanofiber material; Step S4, preparation of a silanol solution: tetraethyl orthosilicate, ethanol and water are mixed at room temperature to obtain a mixed solution, and then the pH value of the mixed solution is adjusted to 2-3 with hydrochloric acid having a concentration of 0.8-1.2 mol / L, and then continuously magnetically stirred at room temperature for 20-25 hours to obtain a silanol solution; Step S5, preparation of flexible fiber aerogel composite thermal insulation material: impregnate the SiO2 nanofiber material and cellulose nanocrystal prepared in step S3 into the silanol solution prepared in step S4, then adjust the pH value to 6-8 with ammonia water with a concentration of 0.4-0.6 mol / L, and after uniform dispersion, seal and stand for aging at 35-45°C for 45-50 hours to obtain a silicon dioxide wet gel; then place the silicon dioxide wet gel in an ethanol solution of trimethylchlorosilane for hydrophobic modification, and then place it in ethanol for solvent replacement, and finally take out the wet gel after solvent replacement, and obtain a flexible fiber aerogel composite thermal insulation material after sufficient drying.
2. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The dispersant in step S1 is one of polyethylene oxide, hexadecyltrimethylammonium chloride and hexadecyltrimethylammonium bromide; the polyethylene oxide is POLYOX WSR N-10 polyethylene oxide from Dow, USA.
3. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The mass ratio of the dispersant and the acidic aqueous solution in step S1 is (0.25-0.35):10; the acidic aqueous solution in step S1 is a nitric acid aqueous solution, and the mass percentage concentration of the acidic aqueous solution is 0.3-0.5%.
4. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The mass ratio of methyltriethoxysilane, tetraethyl orthosilicate and organic solvent in step S1 is 1:2.7:(8-12); the organic solvent is at least one of N,N-dimethylformamide and N,N-dimethylacetamide; the mass ratio of dispersion A to dispersion B in step S1 is 1:(1-2).
5. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The multi-energy field in step S1 is a superposition field of microwaves, steady magnetic fields and electromagnetic oscillation fields; the frequency of the microwaves is 2.0-2.5 GHz, and the power is 400-1000 W; the magnetic field strength of the steady magnetic field is 4000-6000 Gs; the frequency of the electromagnetic oscillation field is 10-20 Hz, and the medium and low duty cycles are 16-20%.
6. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The process parameters of the electrospinning in step S2 include: room temperature 20-26°C, relative humidity 27-33%, voltage 16-22kV, distance between needle tip and receiving device 18-22cm, needle tip swinging distance 90-110mm, injection needle inner diameter 0.51mm, constant feed speed 18-22ml / min, spinning 8-12h.
7. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The inert gas described in step S3 is any one of nitrogen, helium, neon and argon; the molar ratio of tetraethyl orthosilicate, ethanol and water described in step S4 is 1:(8-12):(4-7); the mass ratio of SiO2 nanofiber material, cellulose nanocrystal and silanol solution described in step S5 is (5-8):(1-2):100; the length of the cellulose nanocrystal is 100-500nm and the diameter is 20-100nm.
8. The method for preparing the flexible fiber aerogel thermal insulation material according to claim 1, characterized in that: The mass percentage concentration of the ethanol solution of trimethylchlorosilane in step S5 is 8-12%; the mass ratio of the silicon dioxide wet gel to the ethanol solution of trimethylchlorosilane in step S5 is 1:(4-6); the time for hydrophobic modification in step S5 is 5-8h; the time for solvent replacement is 10-15h; the sufficient drying in step S5 is drying at 60-80°C for 3-5h, washing with deionized water, and then drying at 120-230°C for 4-6h.
9. A flexible fiber aerogel thermal insulation material made by the method for preparing a flexible fiber aerogel thermal insulation material according to any one of claims 1 to 8.
10. Use of the flexible fiber aerogel thermal insulation material according to claim 9 in heating components with complex structures.
Citation Information
Patent Citations
Glass fiber reinforced silicon dioxide aerogel composite material and preparation method thereof
CN101973752A